Rudolf Carnap and the «babylon towers» of world logic - A. V. Nekhaev (Омский научный вестник: Серия "Общество. История. Современность")
The article contains a brief review of the main ideas for such two early Rudolf Carnap’s works as «The Logical Structure of the World and Pseudoproblems in Philosophy» and «The Logical Syntax of Language». It pays an attention to relations between themes and content of these two works, as well as the influence exerted on development of the antimetaphysical investigation of facts program accepted by logical empiricism